Altered umbilical sex steroids in preterm infants born small for gestational age. (16th December 2020) - Allvin, Kerstin; Ankarberg-Lindgren, Carina; Niklasson, Aimon; Jacobsson, Bo; Dahlgren, Jovanna
Abstract: Background: Boys born small for gestational age (SGA) are at increased risk of testicular dysgenesis syndrome, and girls born SGA face the risk of polycystic ovary syndrome later in life. Our aim was to study whether neonates born SGA have an altered profile of steroid hormones at birth. Materials and methods: A total of 168 singletons (99 boys, 69 girls) born at 32.0–36.9 gestational weeks were recruited to a population-based, university hospital, single-center study. Of these, 31 infants (17 boys, 14 girls) were born SGA. The concentrations of dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, dihydrotestosterone, estrone, estradiol, cortisone, and cortisol were analyzed in umbilical cord serum with mass spectrometry. Results: Girls born SGA had higher levels of androstenedione than girls born appropriate for gestational age (AGA) (4.0 versus 2.6 nmol/L, p  = .002). Boys born SGA had lower levels of estrone than boys born AGA (33 822 versus 62 471 pmol/L, p  = .038). Infants born SGA had lower levels of cortisone than infants born AGA, both in girls (340 versus 579 nmol/L, p  = .010) and in boys (308 versus 521 nmol/L, p  = .045). Furthermore, boys born SGA had a higher cortisol/cortisone ratio than boys born AGA (0.41 versus 0.25, p  = .028). Gestational age correlated with DHEAS (boys r  = 0.48, p  = .000, girls r  = 0.35, p  = .013), and cortisol (boys r  = 0.48, p  = .000, girls r  = 0.29, p  = .039). Conclusions: In moderate-to-late preterm infants born SGA, we observed a different steroid hormone profile in cord serum. Girls born SGA show increased levels of androstenedione and boys born SGA show decreased levels of estrone in cord serum, which could be related to placental aromatase deficiency in intrauterine growth restriction.